TANGGUNG JAWAB PENGUSAHA KAPAL ATAS TABRAKAN KAPAL MT SAMUDERA BIRU 168 DENGAN KAPAL MV ROKAN PERMAI BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2008 TENTANG PELAYARAN (STUDI KASUS: PUTUSAN PENGADILAN NEGERI SURABAYA NOMOR 315/PDT.G/2019/PN.SBY) - Yohanes Richardson Braventa; Amad Sudiro (Jurnal Hukum Adigama, 2021)
The seaworthiness of the ship is very much needed because of the many great dangers that will befall the ship with all its contents. Ships that are already in the middle of the ocean, then the ship can be threatened by the dangers caused by rolling waves that cause ship accidents. The problem faced is how is the responsibility of the MV Rokan Permai ship owner for the fire of the MT Samudera Biru 168 Ship due to the collision between the MV Rokan Permai Ship and the MT Samudera Biru 168 ship based on Law Number 17 of 2008 concerning Shipping and how to compensate the victims who suffer losses in the collision of the ship. The research method used is a normative juridical research method. The results show that in the case of a ship collision/collision, the carrier is responsible for the destruction, loss or damage of the goods being transported since the goods are as regulated in Article 40 of Law Number 17 of 2008 Shipping. The settlement of compensation for victims who suffered losses in the ship accident refers to Article 100 paragraph (3) of Law 17 of 2008 concerning Shipping. Regarding the party responsible for the collision accident resulting in a fire, of course there are parties who are responsible. Relevant parties must be responsible in accordance with the authority and responsibility, not only the captain who applies when piloting the ship, but also the carrier company.